2021
DOI: 10.1111/jcmm.15912
|View full text |Cite
|
Sign up to set email alerts
|

The new insight into extracellular NAD+ degradation‐the contribution of CD38 and CD73 in calcific aortic valve disease

Abstract: Nicotinamide adenine dinucleotide (NAD+) is crucial for cell energy metabolism and many signalling processes. Recently, we proved the role of ecto‐enzymes in controlling adenine nucleotide–dependent pathways during calcific aortic valve disease (CAVD). This study aimed to investigate extracellular hydrolysis of NAD+ and mononucleotide nicotinamide (NMN) in aortic valves and aorta fragments of CAVD patients and on the inner aortic surface of ecto‐5′‐nucleotidase knockout mice (CD73−/−). Human non‐stenotic valve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
(84 reference statements)
0
0
3
Order By: Relevance
“…Considering that CD38 can cooperate with CD73 for extracellular ADO production (35), it would be of interest to assess the impact of host CD38 on CD73-mediated tumor cell metabolic fitness. Of note, while some studies suggested that CD73 may hydrolyze extracellular NAD+ (19, 36), we and others (22) did not observe this.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Considering that CD38 can cooperate with CD73 for extracellular ADO production (35), it would be of interest to assess the impact of host CD38 on CD73-mediated tumor cell metabolic fitness. Of note, while some studies suggested that CD73 may hydrolyze extracellular NAD+ (19, 36), we and others (22) did not observe this.…”
Section: Discussioncontrasting
confidence: 72%
“…Considering that CD38 can cooperate with CD73 for extracellular ADO production (35), it would be of interest to assess the impact of host CD38 on CD73-mediated tumor cell metabolic fitness. Of note, while some studies suggested that CD73 may hydrolyze extracellular NAD+ (19,36), we and others (22) did not observe this. Consistent with the observed decrease in intracellular NAD pools, and the importance of NAD for glycolysis (37)(38)(39)(40)(41), we found that CD73-deficient tumor cells also displayed impaired maximal glycolytic capacity following oligomycin treatment, which inhibits ATP synthase and forces cells to redirect pyruvate to lactate conversion via glycolysis (38).…”
Section: Discussioncontrasting
confidence: 71%
“…Considering that CD38 can cooperate with CD73 for extracellular ADO production ( Morandi et al, 2018 ), it would be of interest to assess the impact of host CD38 on CD73-mediated tumor cell metabolic fitness. Of note, while some studies suggested that CD73 may hydrolyze extracellular NAD+ ( Garavaglia et al, 2012 ; Jablonska et al, 2021 ), we and others ( Wilk et al, 2020 ) did not observe this.…”
Section: Discussioncontrasting
confidence: 71%